2022
DOI: 10.1111/ajt.17084
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia reperfusion injury facilitates lung allograft acceptance through IL-33-mediated activation of donor-derived IL-5 producing group 2 innate lymphoid cells

Abstract: Pathways regulating lung alloimmune responses differ from most other solid organs and remain poorly explored. Based on our recent work identifying the unique role of eosinophils in downregulating lung alloimmunity, we sought to define pathways contributing to eosinophil migration and homeostasis. Using a murine lung transplant model, we have uncovered that immunosuppression increases eosinophil infiltration into the allograft in an IL‐5‐dependent manner. IL‐5 production depends on immunosuppression‐mediated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…In lung transplantation, donor tissue NK cells and ILC1s are altered in patients with severe PGD ( 40 ). Conversely, ILC2s and ILC3s may contribute to lung transplant tolerance through a variety of mechanisms ( 41 , 42 ). Here, we found that CD49a + NK cells, likely tissue-resident in origin, trafficked into the airways as they constituted a significant proportion of the sampled BAL NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…In lung transplantation, donor tissue NK cells and ILC1s are altered in patients with severe PGD ( 40 ). Conversely, ILC2s and ILC3s may contribute to lung transplant tolerance through a variety of mechanisms ( 41 , 42 ). Here, we found that CD49a + NK cells, likely tissue-resident in origin, trafficked into the airways as they constituted a significant proportion of the sampled BAL NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…39 These type 2 immune cells support a large group of alternatively activated macrophages that support tissue regeneration and repair, thus protecting against a loss of function during infection. 109 However, a recent study by Guo et al found that the IRI upregulated IL-33, which promoted IL-5 production by graft-resident ILC2s to increase local eosinophils supporting tolerance after lung transplant. 109 Interestingly, this IL-33/IL-5/eosinophil-mediated mechanism relied on immunosuppression to preserve donor ILC2s.…”
Section: Il-33 In Transplantationmentioning
confidence: 97%
“…109 However, a recent study by Guo et al found that the IRI upregulated IL-33, which promoted IL-5 production by graft-resident ILC2s to increase local eosinophils supporting tolerance after lung transplant. 109 Interestingly, this IL-33/IL-5/eosinophil-mediated mechanism relied on immunosuppression to preserve donor ILC2s. These exciting data support the concept that IRI not only triggers pro-inflammatory pathways but also initiates reparative and regenerative mechanisms.…”
Section: Il-33 In Transplantationmentioning
confidence: 97%
“…Furthermore, IL-33 is also known to activate MDSCs to delay heart allograft rejection in mice, which was not investigated by the authors ( 185 , 257 ). Donor-derived ILC2s activated by IRI were recently shown to enhance eosinophil recruitment to the allograft following lung transplantation, leading to reduced T cell infiltration and attenuating rejection at seven days post-transplant ( 261 ). Of note, this axis was dependent on donor ILC2s, rather than infiltrating recipient ILC2s, suggesting additional work will be required to differentiate the roles of donor and recipient ILC2s in other transplant models ( 261 ).…”
Section: Engineering Tolerance and The Development Of Innate Immune C...mentioning
confidence: 99%